Paeonol Inhibits Oxidized Low-Density Lipoprotein-Induced Vascular Endothelial Cells Autophagy by Upregulating the Expression of miRNA-30a - Li, Chao; Yang, Li; Wu, Hongfei; Dai, Min (Frontiers in Pharmacology, 2018)
Paeonol from Cortex Moutan root is a potential therapeutic agent for atherosclerosis (AS). However, its mechanisms of action are still not fully understood. Vascular endothelial cells (VECs) autophagy plays a vital role in the initiation and progression of AS. In this study, we aim to investigate whether the protective effect of paeonol on ox-LDL-induced VECs injury by regulating autophagy. To address this question, we used ox-LDL-induced rat VECs as a model system to elucidate the protective effect of paeonol on VECs injury. This study displayed that ox-LDL (100 mg/L) treatment inhibited VEC growth in dose- and time-dependent manners, paeonol (60 μM) shown potential in inhibiting ox-LDL-induced death. Furthermore, paeonol significantly reduced ox-LDL-induced the formation of autophagy vacuoles and the expression of LC3II in VECs. Further double-luciferase reporter assay shown that miR-30a specifically binds to the 3′-UTR of Beclin-1 mRNA in VECs. Moreover, we found that ox-LDL decreased miR-30a and increased Beclin-1 expression, pretreatment with paeonol could reverse the process of regulation